Adrenergic Contribution During Acclimatization to High Altitude: Perspectives from Pikes Peak - Mazzeo, R. S.; Reeves, J. T. (Exercise and Sport Sciences Reviews, 2003)
A dissociation of sympathoadrenal responses during acclimatization to 4300 m contributes significantly to key metabolic and physiologic adjustments necessary to adapt to high-altitude exposure.